Determinants of Inflation in Sri Lanka after Economic Liberalization: An Econometric Analysis - Kesavarajah, M. (University of Colombo, 2011)
Introduction Despite Sri Lanka achieving a substantial rate of economic growth over the past three decades, it remains far from optimal regarding some of its macroeconomic indicators. Since trade liberalization and other market-oriented reforms, Sri Lanka has come almost a full circle with respect to economic policy regimes. During this period, the trend of inflation recorded in Sri Lanka has been highly volatile and has emerged as the most common problem all over the country. As measured by the Colombo Consumer Price Index, inflation increased from 16.6 percent in 1984 to 21.5 percent in 1990. Since 1990, the rate decreased gradually until 1995. From 1995 to 2002 the inflation rate was low. However, after 2003, the inflation rate has been increasing gradually again until 2008. In year 2008, the inflation rate recorded was at a peak at 22.6 percent. During the above period, various factors contributed to this highly volatile situation. Particularly the growth of money supply, interest rate, budget deficit and depreciation of the Sri Lankan currency against the dollar contributed to this outcome. Further, structural factors have also had an impact on this high level of inflation. This study however only attempts to analyze the experience of inflation after trade liberalization through focusing on the main factors influencing the rate of inflation in Sri Lanka